Would adults with autism be less likely to bury the survivors?: An eye movement study of anomalous text reading - Au-Yeung, SK; Kaakinen, JK; Liversedge, SP; Benson, V (SAGE Publications, 2018)
In a single eye movement experiment, we investigated the effects of context on the time course of local and global anomaly processing during reading in adults with Autism Spectrum Disorder (ASD). In one condition, short paragraph texts contained anomalous target words. Detection of the anomaly was only possible through evaluation of word meaning in relation to the global context of the whole paragraph (Passage-Level Anomalies). In another condition, the anomaly could be detected via computation of a local thematic violation within a single sentence embedded in the paragraph (Sentence-Level Anomalies). For the sentence-level anomalies, the ASD group, in contrast with the typically developing (TD) group, showed early detection of the anomaly as indexed by regressive eye movements from the critical target word upon fixation. Conversely, for the passage-level anomalies, and in contrast with the ASD group, the TD group showed early detection of the anomaly with increased regressive eye movements once the critical word had been fixated. The reversal of the pattern of regression path data for the two groups, for the sentence- and passage-level anomalies, is discussed in relation to cognitive accounts of ASD.